Graphene Oxide and Reduced Graphene Oxide Exhibit Cardiotoxicity Through the Regulation of Lipid Peroxidation, Oxidative Stress, and Mitochondrial Dysfunction - Zhang, Jian; Cao, Hong-Yan; Wang, Ji-Qun; Wu, Guo-Dong; Wang, Lin (Frontiers in Cell and Developmental Biology, 2021)
Objective: Graphene has been widely used for various biological and biomedical applications due to its unique physiochemical properties. This study aimed to evaluate the cardiotoxicity of graphene oxide (GO) and reduced GO (rGO) in vitro and in vivo, as well as to investigate the underlying toxicity mechanisms. Methods: GO was reduced by gamma irradiation to prepare rGO, and then characterized by UV/visible light absorption spectroscopy. Rat myocardial cells (H9C2) were exposed to GO or rGO with different absorbed radiation doses. The in vitro cytotoxicity was evaluated by MTT assay, cell apoptosis assay, and lactate dehydrogenase (LDH) activity assay. The effects of GO and rGO on oxidative damage and mitochondrial membrane potential were also explored in H9C2 cells. For in vivo experiments, mice were injected with GO or rGO. The histopathological changes of heart tissues, as well as myocardial enzyme activity and lipid peroxidation indicators in heart tissues were further investigated. Results: rGO was developed from GO following different doses of gamma irradiation. In vitro experiments in H9C2 cells showed that compared with control cells, both GO or rGO treatment inhibited cell viability, promoted cell apoptosis, and elevated the LDH release. With the increasing radiation absorbed dose, the cytotoxicity of rGO gradually increased. Notably, GO or rGO treatment increased the content of ROS, as well as reduced the mitochondrial membrane potential in H9C2 cells. In vivo experiments also revealed that GO or rGO treatment damaged the myocardial tissues, as well as changed the activities of several myocardial enzymes and the lipid peroxidation indicators in the myocardial tissues. Conclusions: GO exhibited a lower cardiotoxicity than rGO due to the structure difference, and the cardiotoxicity of GO and rGO might mediated by lipid peroxidation, oxidative stress, and mitochondrial dysfunction.